Порівняння схем модуляцій для систем зв'язку 5G і 6G - Фесенко, А. В. (ХНУРЕ, 2023)
The report provides an overview of modulation schemes used in 5G/IMT-2020 and 6G wireless communication systems. The main focus is on modulation techniques used at the physical layer of these systems. The report explores the advantages and disadvantages of different modulation schemes and their suitability for 5G/IMT-2020 and 6G systems.
Keywords: схеми модуляцій; система зв'язку 5G